ChemInform Abstract: A General Route to 1, 3′‐Bipyrroles. Issue 20 (20th May 2014) - Cheng, Ping; Shao, Wenjie; Clive, Derrick L. J.
Abstract Several differently substituted 1, 3‐bipyrroles are prepared by this method and subsequent modifications.